Place and role of consumer experience in WWW information environment - Тимовчак-Максимець, Оксана Юріївна; Пелещишин, Андрій Миколайович (Eastern-European Journal of Enterprise Technologies, 2012)
In the paper the features of user-generated content are described and characteristics that stipulate its social value are defined. The definition of "consumer experience" notion is suggested and the place of this information layer among other layers of subjective user information is defined